Autoestima en la adolescencia: análisis y estrategias de intervención - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (International Journal of Psychology and Psychological Therapy, 2012)
Self-Esteem in Adolescence: Analysis and Intervention Strategies. This paper reviews the current state of research on self-esteem by focusing on the factors that are relevantfor the intervention in adolescents. Firstly, a conceptual distinction is made between self-concept, self-esteem and the perception of self-worth, and the relationship between them is analysed. It also considers the functioning of self-esteem on the basis of the contingencies of reinforcement and reviews their effects on the cognitive styles and behavioural coping.Secondly, it reviews the course of self-esteem on the basis of gender and discusses the role that contingencies of reinforcement play on its decline and instability during early adolescence. Thirdly, it reviews the findings that show the relationship of the short comings of self-esteem and the generation of a series of behavioural, emotional and health problems. Finally, the findings of the research on the intervention in self-esteem are reviewed, and the most useful strategies to help promote a change in teenagers are discussed.
Keywords: Autoestima; Adolescentes - Psicología; Autoconcepto; Contingencias de autovalía; Intervención psicológica